2011
DOI: 10.5054/tj.2011.250380
|View full text |Cite
|
Sign up to set email alerts
|

“Listen to My Story and You Will Know Me”: Digital Stories as Student‐Centered Collaborative Projects

Abstract: This article explores the power of English language learners' digital stories as student‐centered projects and offers practical suggestions for language teachers interested in trying digital storytelling. The article explains pedagogical practices and digital storytelling in the context of contemporary scholarship on inclusive pedagogy, communities of practice, and multiliteracies. As students develop and produce their stories, they not only choose topics, visual images, and musical materials that are meaningf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 13 publications
2
35
0
4
Order By: Relevance
“…For example, ESL or EFL teachers of large classes could create collaborative pair or group digital storytelling projects that are shorter in length and could invite other teachers (e.g., media specialists or content-area teachers) to integrate digital storytelling into a thematic unit as part of an interdisciplinary project. Regardless of the modifications that teachers make in their contexts, providing specific guidance to students throughout the digital storytelling process and creating a collaborative environment in which both students and the teachers learn from one another (Vinogradova, Linville, & Bickel, 2011) are essential to an efficacious multiliteracies pedagogy.…”
Section: Resultsmentioning
confidence: 99%
“…For example, ESL or EFL teachers of large classes could create collaborative pair or group digital storytelling projects that are shorter in length and could invite other teachers (e.g., media specialists or content-area teachers) to integrate digital storytelling into a thematic unit as part of an interdisciplinary project. Regardless of the modifications that teachers make in their contexts, providing specific guidance to students throughout the digital storytelling process and creating a collaborative environment in which both students and the teachers learn from one another (Vinogradova, Linville, & Bickel, 2011) are essential to an efficacious multiliteracies pedagogy.…”
Section: Resultsmentioning
confidence: 99%
“…Although research generally has highlighted how digital storytelling can be a powerful tool of self‐representation (see, e.g., Lenette, Cox, & Brough, ), some scholars specifically have drawn attention to its inherent multimodal properties. For example, Vinogradova, Linville, and Bickel () demonstrated how working with various artifacts in a digital storytelling project can foster the development of ELs’ multimodal design skills as they learn to purposively use different modes to create meaning. Hull and Katz () argued that the use of multiple resources in digital storytelling enables individuals to express key events in their lives from a position of strength.…”
Section: Digital Storytelling As a Multimodal Pedagogymentioning
confidence: 99%
“…Others examined digital storytelling in L2 classrooms. Sadik (2008) explored the use of digital stories in various content areas including English as a foreign language (EFL) while Cloud, Lakin, and Leininger (2011) and Vinogradova, Linville, and Bickel (2011) documented the use of digital storytelling with adolescent and adult English language learners (ELLs). These studies found that digital stories can advance cognitive development, self-authoring, and identity construction (Davis, 2004;Sadik, 2008).…”
Section: The Gift Of Voicementioning
confidence: 99%